INITIAL LANGUAGE LEARNER PROFILES AND KRASHEN'S HYPOTHESES - Tukhtaeva Zarina (Bright Mind Publishing, 2025)
This paper presents the initial language learner profiles of two students, Anna and Alex, at a multilingual language center. The study reflects on teaching experiences with learners of A1 level, explores their learning challenges and progress, and connects their development to key second language acquisition theories such as Krashen’s Input Hypothesis, the Natural Order Hypothesis, and the Affective Filter Hypothesis. The reflection also discusses practical classroom approaches to support learner motivation and engagement.
Keywords: Second language acquisition, Input Hypothesis, Natural Order Hypothesis, Affective Filter, learner profiles, multilingual education, CEFR.